Características Del Buen Profesor De Modalidad Presencial Y Virtual Desde La Perspectiva De Los Estudiantes - Castillo, Mirsha Alicia Sotelo; García, Javier José Vales; López, Ramona Imelda García; Hernández, Laura Fernanda Barrera (European Scientific Journal, ESJ, 2017)
The purpose of the study was to identify the characteristics associated to the good teacher who teaches presential and virtual mode. A total of 713 students participated, distributed in two groups (493 and 220), from different academic programs of a Mexican institution of higher education participated. For data collection, the technique of semantic networks was used, they were presented as stimulus phrase "good presential teacher" and "good virtual teacher". Two semantic networks were obtained, one for presential teacher, generating 269 definers and a network core of 39. The other semantic network was for the virtual teacher, where 118 words and a network nucleus of 37 were generated. The three words that resulted in greater semantic weight were: responsible, respectful and comprehensive for the presential, accessible and available for the virtual. This study concludes that the definition the students do of the good teacher, regardless of the modality, is determined by personal values.